Using Flipped Classroom Method To Improve Students’ Writing Recount Text For Eight C-Grade At Smp Islam Al Azhaar Tulungagung - Siti Khoirunisa; Bekti Wirawati; Erna Sulistyawati (Reforma : Jurnal Pendidikan dan Pembelajaran, 2022)
The research is intended to: show how flipped classroom method can improve the students’ writing recount text for eight c grade at SMP Islam Al Azhaar Tulungagung. This research used classroom action research as suggested by Kemmis and Mc Taggart in Burn (2005) . The population of this research was the eighth grade students which consisted of 123 students for eighth grade. Sample this research is VIII C which 23 students. The data were taken quantitative data were taken from the writing test. Based on the result of the research that had been done in three, the students  could write easily without consuming more time because they were arranging and writing recount text based watching video. It showed by the score of pre-test and post-test each cycle. In the pre-test found the total score of students’ writing result was 21 students low in score test. In the first until third cycle found the total score of students’ writing result was 15, 7 & 2 student low in score test. In teaching learning process, more student have passed the KKM.